Microstructurally engineered nanocrystalline Fe-Sn-Sb anode : towards stable high energy density sodium-ion batteries - Edison, Eldho (2020)
To facilitate the commercialization of sodium-ion batteries (SIBs), advanced electrode materials with high sodiation capacities and enhanced cycling stabilities are essential. Herein, we investigate the effect of Fe incorporation into SnSb to generate a new ternary nanocrystalline composite based anode, which improves the cycling stability and performance of SIBs. We ensure a high-throughput synthetic approach via a rapid-solidification technique for efficient and industrially viable Fe–Sn–Sb alloy synthesis. Interestingly, the new ternary system possesses nanocrystalline domains that helped to alleviate the stresses induced upon the sodiation/desodiation reactions and thereby enhanced the performance. The Fe1.0–SnSb anode delivered a capacity of ∼500 mA h g−1 at a specific current density of 50 mA g−1 for over 120 cycles and a full-cell was designed, which could deliver one of the highest reported energy densities of ∼826 W h kganode−1. The promising electrochemical results assert the significance of microstructural engineering of alloying anodes and open up new avenues of research into rapidly solidified alloys for energy storage applications.